THE USE OF QUALITATIVE APPROACH IN INFORMATION SYSTEM RESEARCH - Nugroho, Rino Ardhian; Prakoso, Septyanto Galan; Astuti, Theresia Adinda Kusuma; Hidayati, Kartika Nur; Utomo, Is Hadri; Hanifah, Roisa Nur (DIA: Jurnal Administrasi Publik, 2024)
During the pandemic, several governments choose to emphasize the strict approach to immigration on their border. This approach focuses on screening, tracing, and quarantine mechanisms. One of the countries that prioritize this method rather than relying on vaccination is Taiwan. This approach is also heavily affected by information technology advancement in government. This paper will discuss the implementation of digital fencing in Taiwan, using a qualitative method and personal narrative elaboration. The informants of this study are foreigners who entered and exited Taiwan during the COVID-19 pandemic and will provide a lot of resourceful data based on their experience. The result indicates that the socio-technical approach helps Taiwan in implementing digital fencing to reduce the risk of COVID-19.